The Research on the Effect of Humidity on the Rheological Model of Swelling Rock - Ming Ji; Yi-Dong Zhang (Advances in Civil Engineering)
The research on the rheological mechanical behaviour of swelling rock in the condition of humidity field has a significant meaning for large rock engineering, such as deep coal mining, tunnelling, and slope engineering. Based on the Nishihara model, considering on the effect of humidity factor on swelling rock, the rheological elements are established and the effects of humidity on the damage of rock, the viscosity, and the elasticity are introduced. Moreover, the viscoelastic plasticity constitutive equations are established under the coupling of swelling rock stress and humidity. Afterward, considering the effects of humidity on the damage, elasticity, and viscosity, the creeping, unloading, and relaxation equations have been deduced. From this research, under the state of low stress σ3P<σS, the Nishihara model which considers the effect of humidity shows the properties of stable creeping. In addition, the unloading curves contain instantaneous elasticity, elastic after effect, and the viscosity flow induced by the humidity. However, under the state of high stress σ3P≥σS, it is an unstable creeping model. The unloading curves include instantaneous elasticity, elastic after effect, and the viscosity flow induced by the stress and the humidity. This model reflects the rheological properties of swelling rock comprehensively, and it can be used for rock rheological analysis.